The Condition of Arboriflora of the Gvardejskij Park of Krasnoyarsk - Maria A. Kirienko; Larisa N. Skripal’shchikova; Irina A. Goncharova (Лесной журнал)
An inventory of green spaces in the Gvardejskij Park of the Sovetskij District of Krasnoyarsk has been carried out. The aim of the work has been to assess the species composition and vital condition of woody and shrubby vegetation in the territory of this park. The study was carried out in the summer of 2020. The species diversity, vital and sanitary condition of the woody and shrubby vegetation has been assessed by the complete enumeration method. The vitality index of green spaces has been determined using the generally accepted method of visual assessment of woody and shrubby vegetation. It has been established that the park is home to 38 plant species (19 trees and shrubs each) belonging to 30 genera of 17 families. The plants are arranged in the form of alley and group plantings, solitaires, bosquets, and are also included in hedges. The vitality index of the park’s plantings is 1.93 for plants in the composition of alley and group plantings, solitaires and bosquets, which corresponds to a weakened or slightly damaged condition, and 1.28 for hedge plants – a healthy planting. Based on the results of the study, the structure of the park’s plantings, its features, and the species that make the main quantitative contribution to it have been determined. The most weakened species and the reason for their weakening have been identified. Of the woody plants in the park, balsam poplar and Siberian elm are weakened, which is due to the age of the plantings. The weakened condition of Siberian larch is caused by massive infestation by larch bud gall midge. The conclusion has been made about the lack of timely care for plants, which has led to deterioration in the vital condition of many species. Species that are most resistant to adverse factors associated with growing in urban conditions have been identified. Based on the analysis of the results obtained, recommendations have been formulated to improve the condition of the plantings of the Gvardejskij Park.